Effective Natural Supersymmetry from the Yukawa Deflected Mediations. (10th July 2017) - Liang, Tai-ran; Zhu, Bin; Ding, Ran; Li, Tianjun
Abstract : The natural supersymmetry (SUSY) requires light (≤1 TeV) stop quarks, light sbottom quark, and gluinos. The first generation of squarks can be effectively larger than several TeV which does not introduce any hierarchy problem in order to escape the constraints from LHC. In this paper we consider a Yukawa deflected mediation to realize the effective natural supersymmetry where the interactions between squarks and messengers are made natural under certain Froggatt-Nielsen U ( 1 ) X charges. The first generation squarks obtain large and positive contribution from the Yukawa deflected mediation. The corresponding phenomenology and sparticle spectra are discussed in detail.